2020
DOI: 10.3390/agriculture10120607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genotype × Environment Interaction for Seed Traits in Winter Oilseed Rape (Brassica napus L.)

Abstract: Brassica napus (L.), winter oilseed rape (WOSR) or canola, is one of the most important oilseed crop species of the moderate climate zone. Improving the seed quality and yield makes the main target in breeding programs worldwide. In this study, we examined the genotype-by-environment (G×E) interaction with respect to six seed traits among 25 WOSR genotypes. The plant material included the registered canola cultivars, our newly developed mutant breeding lines and the Ogura F1 hybrids and their parental componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…On the other hand, GE interactions were significant for two of the three traits of interest (seed yield and pod per plant) and explained 18.1% of the variation in seed yield and 11.3% for pods plant −1 . Recent research assessing GE interaction for canola has mostly focused on seed quality traits (Bocianowski et al., 2019; Liersch et al., 2020). However, Załuski et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, GE interactions were significant for two of the three traits of interest (seed yield and pod per plant) and explained 18.1% of the variation in seed yield and 11.3% for pods plant −1 . Recent research assessing GE interaction for canola has mostly focused on seed quality traits (Bocianowski et al., 2019; Liersch et al., 2020). However, Załuski et al.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, GE interactions were significant for two of the three traits of interest (seed yield and pod per plant) and explained 18.1% of the variation in seed yield and 11.3% for pods plant −1 . Recent research assessing GE interaction for canola has mostly focused on seed quality traits (Bocianowski et al, 2019;Liersch et al, 2020). However, Załuski et al (2020) reported significant environmental, genotypic, and GE interactions effects on seed yield and 1000-seed weight in camelina [Camelina sativa (L.)], a member of the Brassicaceae family.…”
Section: Genotype By Environment Interactionmentioning
confidence: 99%
“…Oilseed rape ( Brassica napus L.) is the second worldwide major supplier of edible oil, after soybeans (Liersch et al, 2020 ). The oilseed rape grain production reached almost 71 million tons during the 2018–2019 cropping season (Liersch et al, 2020 ). In Iran, however, oilseed rape is the first major oilseed cultivated crop (Amiri Oghan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The factors affecting oil yield could be oil content, seed water content, and pressing technology [40][41][42]. Oilseed content in general is affected by the interaction between genetic and environmental factors [43,44]. The existence of seed water content affects the oil quality (clearness of the oil yield) [42], while the pressing technology could affect the oil yield due to differences in the pressure strength [41].…”
Section: Oil Yield and Oil Quality Of Sacha Inchimentioning
confidence: 99%